Energy Supply to Isolated Areas: Attracting Investment and Developing Regional Economy - Asaul, Anatoliy N.; Asaul, Maksim A.; Levin, Yuri A.; Platonov, Anatoliy M. (Economy of Regions, 2020)
The study analyses energy supply to isolated areas considering the development of priority areas of the regional economy and assessing the dependence between consumer finances and electricity costs. We examined energy supply problems in the example of the Tuva Republic, the Russian region with vast isolated areas and high prices for energy. We explained the reasons for the increase in electricity costs, including small-scale generation sources based on fossil fuels. The limitations of economically substantiated energy transmission at light loads prevent the connection to a centralised energy supply systems in isolated territories, leading to a decentralised energy supply. Thus, we proposed a methodological toolkit for solving the problem of economic substantiation of the dependence between consumer finances and electricity costs, testing it on the example of the gold mining industry. Our hypothesis relies on technological development opportunities in the field of renewable energy sources to reduce the construction and operation costs of generation facilities. Since the economic feasibility of using renewable energy sources for investors is determined by the dependence of consumer finances on energy generation costs, it is necessary to create energy resource structures depending on different basic conditions. For that purpose, we showed the linear dependence of the profitability of gold mining investment projects on electricity costs. The proposed criteria and methods allow determining the threshold values of the economic efficiency of energy services provided by suppliers and energy produced by self-generating facilities. Based on these results, further research can focus on analysing the impact of electricity costs on the financial parameters of projects to apply innovative energy supply schemes and identifying thresholds of the response of profitability to energy costs reduction for different energy consumption projects.